Learning Guidance As Business Opportunities In Educational Entrepreneurship - Ayu Gede Willdahlia; Ni Kadek Nita Noviani Pande; Aniek Suryanti Kusuma; Desak Dwi Utami Putra (Institute of Computer Science (IOCS), 2022)
This study aims to examine articles related to tutoring as a business opportunity in the field of education. study of literature by outlining or describing literature relevant to the topic of guidance and information synthesis that focuses on the findings then summarizes the substance of the literature and draws conclusions from the contents of the literature. . The use of technology in the application of online tutoring must pay attention to the appearance of the site/application so that it is easy for customers to use. There is still a need for parental assistance for children who follow tutoring. Tutoring makes it easier for students to learn, thus changing the learning paradigm so far, if all this time learning tends to occur in the classroom when teachers and students interact, then with the presence of online tutoring that presents an online-based learning process in the form of applications, so that students find it easier to access learning materials.